Components of the New Intellectual Field: Education and Pedagogy in Venezuela (1994-2000) - Arellano Duque, Antonio (Education Policy Analysis Archives, 2005)
This investigation is inscribed in the field of school reform and proposes to use the concept of Intellectual Field of Education and Pedagogy as a meaningful approach to study educational and pedagogical changes happening in Venezuela during the years 1994- 2000. This study reconstructs thematic universes through content analysis of key documents and discourses about education to identify the relevant paradigms and general tendencies in educational development.